Perceived threat of COVID-19 and future travel avoidance - Turnšek, Maja (Academica turistica, 2020)
The present study provides a snapshot of Slovenian tourists' perceptions in a historically unique point of time - the early days of the covid-19-related lockdown. Based on an online survey performed in March and April 2020 the study provides first insights into Slovenian tourists% perceived threats of covid-19 on two dimensions: severity and susceptibility; how this depends on their demography and past travel experience and what, in this specific point in time, they think about future travel avoidance. The results have shown that age affects the two measured dimensions of perceived threat and future travel avoidance, but only with women. Furthermore, people who have travelled the most in the past express the least likelihood of avoidance to travel due to the covid -19 pandemic. Those who are more educated, on the other hand, perceive higher risk, yet education has no role in their expressed future travel avoidance. The results, moreover, show that the moral obligation towards taking care of others might be a highly important element in the success factor of covid-19 measures and thus future appeals by the tourism industry. Finally, the results show that we cannot easily predict how the general population will behave regarding their future travel avoidance since the opinions are not polarised in the extremes. This does indicate, however, that tourists will be susceptible to the context-specific factors of future travel decisions, such as assurances of health safety provided by the tourism industry.
Keywords: COVID-19; fear appeals; future travel avoidance; health threat perception; potovanja; tourism; turizem; zdravje